2022
DOI: 10.3390/metabo12090775
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Plasma Metabolomics and Intestinal Microbiome in db/db Mouse, an Animal Model for Study of Type 2 Diabetes and Diabetic Kidney Disease

Abstract: Evidence has demonstrated that either metabolites or intestinal microbiota are involved in the pathogenesis of type 2 diabetes (T2D) and diabetic kidney disease (DKD). To explore the interaction between plasma metabolomics and intestinal microbiome in the progress of T2D-DKD, in the current study, we analyzed metabolomics in the plasma of db/db mice with liquid chromatography–mass spectrometry and also examined intestinal prokaryotes and entire gut microbiome dysbiosis at the genus level with both 16S rDNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…By studying the interaction between the gut microbiome and plasma metabolomics in an experimental model of DN in mice, evidence supporting the existence of the gut-kidney axis has been found. This study confirmed the involvement of gut microbiota and circulating metabolites in the progression of DN ( 41 , 42 ). It is noteworthy that imbalanced gut microbiota is found in DN patients’ fecal samples where there is an increased presence of Proteobacteria , Verrucomicrobia and Fusobacteria ( 43 ).…”
Section: Discussionsupporting
confidence: 84%
“…By studying the interaction between the gut microbiome and plasma metabolomics in an experimental model of DN in mice, evidence supporting the existence of the gut-kidney axis has been found. This study confirmed the involvement of gut microbiota and circulating metabolites in the progression of DN ( 41 , 42 ). It is noteworthy that imbalanced gut microbiota is found in DN patients’ fecal samples where there is an increased presence of Proteobacteria , Verrucomicrobia and Fusobacteria ( 43 ).…”
Section: Discussionsupporting
confidence: 84%
“…16S rDNA, metagenomics, and mass spectrometry can be utilized to explore the diversity, composition, and function of gut microbiota as well as microbiota-related serum metabolites in patients with DKD. Interaction studies between plasma metabolomics and gut microbiome in experimental DKD mouse/rat model provided evidence for the gut-metabolism-kidney axis, and verified the involvement of gut microbiota and circulating metabolites in DKD progression (15,16). DKD patients displayed dysbiosis with composition, richness and diversity in gut microbiota (17)(18)(19).…”
Section: Gut Microbiota and Its Metabolites Gut Microbiotamentioning
confidence: 78%
“…The kidney is the main organ for extensive metabolization and clearance of small molecules. Therefore, metabolomics is a precious approach in the research of kidney diseases, for example diabetic kidney disease, CKD and gout renal injury 18,34,35 . Changes in the serum or urine metabolites concentration may result from impaired kidney functions and can be used as predictors of kidney diseases.…”
Section: Discussionmentioning
confidence: 99%